2013
DOI: 10.1002/etc.2307
|View full text |Cite
|
Sign up to set email alerts
|

The acute toxicity of chemically and physically dispersed crude oil to key arctic species under arctic conditions during the open water season

Abstract: The acute toxicity of physically and chemically dispersed crude oil and the dispersant Corexit 9500 were evaluated for key Arctic species. The copepod Calanus glacialis, juvenile Arctic cod (Boreogadus saida), and larval sculpin (Myoxocephalus sp.) were tested under conditions representative of the Beaufort and Chukchi Seas during the ice-free season. The toxicity of 3 water-accommodated fractions (WAF) of Alaska North Slope crude oil was examined with spiked, declining exposures. A dispersant-only test was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 61 publications
7
65
1
Order By: Relevance
“…We modeled two scenarios: physically dispersed oil and 100% chemically dispersed oil using COREXIT® 9500. Gardiner et al (2013) measured LC 50 values of 80 ppb PAH (polynuclear aromatic hydrocarbons) when Arctic cod juveniles were subjected to physically dispersed oil alone and 1640 ppb PAH when subjected to oil plus dispersant (chemically dispersed oil). These were the LC 50 values for the breaking wave water accommodated fraction (BW-WAF) and the chemically enhanced water accommodated fraction (CE-WAF) described by Gardiner et al (2013).…”
Section: Oil Spill Scenariosmentioning
confidence: 99%
See 3 more Smart Citations
“…We modeled two scenarios: physically dispersed oil and 100% chemically dispersed oil using COREXIT® 9500. Gardiner et al (2013) measured LC 50 values of 80 ppb PAH (polynuclear aromatic hydrocarbons) when Arctic cod juveniles were subjected to physically dispersed oil alone and 1640 ppb PAH when subjected to oil plus dispersant (chemically dispersed oil). These were the LC 50 values for the breaking wave water accommodated fraction (BW-WAF) and the chemically enhanced water accommodated fraction (CE-WAF) described by Gardiner et al (2013).…”
Section: Oil Spill Scenariosmentioning
confidence: 99%
“…The panel concluded that data on the relative toxicity of crude oil and dispersed oil to pelagic and epipelagic organisms in the Arctic were limited and that additional toxicity data based on Arctic organisms tested under Arctic conditions were needed. This led to a toxicity research program as reported by Gardiner et al (2013). The acute toxicity of physically and chemically dispersed crude oil was evaluated for three Arctic species: the copepod Calanus glacialis, juvenile Arctic cod (Boreogadus saida), and larval sculpin (Myoxocephalus sp.).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, in an emergency context such an oil spill, it is necessary to have as soon as possible toxicity data to evaluate the potential biological impact. Many studies have evaluated the acute toxicity of dispersant alone [3][4][5][6] or dispersant enhanced water accommodated fractions [7][8][9][10]. These methods presented a major disadvantage.…”
Section: Introductionmentioning
confidence: 99%